China's political worldview and Chinese exceptionalism: international order and global leadership - Ho, Benjamin ca. 20./21. Jh. (Transforming Asia, 2021)
This book uses the notion of "Chinese exceptionalism" as a framework to analyze China's international politics and foreign policy. It argues that China's approach to international relations is best understood in the context of these claims to exceptionalism and China's broader political world view. In doing so, it fosters a more comprehensive understanding of China's actions within the realms of foreign policy and international politics, and in the context of the preferred world order, norms and rules that the country seeks to promote